Insect pests of some exotic and indigenous browse species in southeastern Nigeria - Orok, E.J.; Ekpo, M.U.; Larbi, Asamoah (Springer, 1995)
During the period February to July 1992, the incidence of attacks by insect pests on ten cultivated browse species was studied at Obio Akpa, located in humid southeastern Nigeria. Two of the browse species Gliricidia sepium and Leucaena leucocephala were exotic and eight Alchornia cordifolia, Baphia nitida, Rauvolfia vomitoria, Diallum guineensis, Ficus capensis, Glyphaea brevis, Homalium aylmeri and Manniophytum fulvum indigenous. Forty insect pests were collected and 33 identified. Those identified belonged to either the order Coleoptera, Heteroptera, Lepidoptera or Orthoptera. Some of the insects were browse-specific, while others attacked several browse species. None of the browse species was free from insect attacks.